2014
DOI: 10.1007/s00380-014-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of renal function on the association of rs854560 polymorphism of paraoxonase 1 gene with long-term prognosis in patients after myocardial infarction

Abstract: Paraoxonase 1 (PON1) is an enzyme responsible for the antioxidant properties of high density lipoprotein (HDL). The activity of PON1 is decreased in patients with coronary artery disease, myocardial infarction or chronic kidney disease. rs662 and rs854560 are single nucleotide polymorphisms (SNPs) associated with PON1 activity and 10-year cardiovascular mortality of patients with stable coronary artery disease. We investigated the association of rs662 and rs854560 SNPs of the PON1 gene with 5-year mortality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As described previously [1820], the registry included consecutive patients with STEMI admitted to our department in the years 2001–2005 and treated invasively within 12 h from symptoms onset. On the day of admission, after obtaining informed written consent, blood samples were collected.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously [1820], the registry included consecutive patients with STEMI admitted to our department in the years 2001–2005 and treated invasively within 12 h from symptoms onset. On the day of admission, after obtaining informed written consent, blood samples were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The rs662 SNP leads to transition between adenine and guanine nucleobases that results in glutamineto-arginine substitution at codon 192 (Q192R) [12]. The genotype AA is linked with an unfavorable lipid status and low PON1 activity in patients [13]. However, the associations of PON1 polymorphism with CAS risk remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the polymorphisms did not show any significant association with the prognosis of CAD or the results were controversial. On the other hand, several papers reported promising results; for example, genome-wide association study (GWAS) identified polymorphisms in loci 1p13.3 (rs599839), 1q41 (rs17465637), and 3q22.3 (rs9818870) [ 7 ], or the variants of paraoxonase 1 gene (rs854560) [ 5 ] and phospholipase A2 gene (rs1805017) [ 6 ]. These data were repetitively confirmed by following studies [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%